Comparative Genome and Transcriptome Study of the Gene Expression Difference Between Pathogenic and Environmental Strains of Prototheca zopfii - Zeng, Xuanhao; Kudinha, Timothy; Kong, Fanrong; Zhang, Qiang-qiang (Frontiers in Microbiology, 2019)
Prototheca zopfii commonly exists in the environment, and causes invasive infections (protothecosis) in humans. The morbidity of protothecosis has increased rapidly in recent years, especially in systemic infections of patients with an impaired immune system. The infection in immunocompromised patients has a poor prognosis due to limited understanding of the pathogenesis of the disease, as most previous studies mainly focused on classification and recognition of pathogenic strains. In this study, we constructed the genome and transcriptome of two pathogenic strains and one environmental strain, by next generation sequencing methods. Based on our preliminary gene expression findings, genes in P. zopfii pathogenic strains are significantly up-regulated in metabolism in peroxisome, such as glyoxylate cycle, which may improve the organism’s resistance to the harsh environment in phagolysosome of macrophage and its ability to survive in an anaerobic environment. We also found some significant up-regulated genes, which are related to adherence and penetration in dermatophytes, and we speculate that this may enhance the virulence capacity of pathogenic strains. Finally, the genomes and transcriptomes of P. zopfii described here provide some base for further studies on the pathogenesis of this organism.